Strategizing the magnetic technologies - Puteri Fadzline, Muhamad Tamyez; M.R, Kamaruddin (Universiti Utara Malaysia, 2020)
Innovation has been a platform from various industries not only to increase better company’s performance, but also to reduce cost and increase profit. This has been the case for CAV Technologies Sdn Bhd, which involves the customers right from the start in the development of their products. Even though CAV is one of the leading companies in the field of development, production and application of know-how of magnetic materials, they are also affected in the turbulence of the Covid-19 pandemic, where they were forced to seek lower costs which include manpower costs. In September 2020, Mr Azlan and his team pondered about the best technology strategy that the company could remain as a dominant player in the magnetic technology industry.